Evaluasi Penggunaan Gliserol dalam Pembuatan Preparat Telur Cacing Semipermanen - Shinta Asarina; Nuni Haeruni (UPT Laboratorium Terpadu, Universitas Diponegoro, 2019)
Glycerol is one of the ingredients for preserving bacterial culture. Glycerol has hygroscopic properties so that it can absorb water molecules from the environment and prevent wet mount preparations. The use of glycerol in making semipermanent worm egg preparations for microscopic examination was evaluated in this study. This research was conducted at the Microbiology and Parasitology Laboratory of the Faculty of Medicine, Padjadjaran University, Bandung. From the results of the study it was found that worm egg preparations with the addition of glycerol can last longer than those without glycerol. This method can be recommended for making semipermanent worm egg preparations for the purpose of parasitological examination in the laboratory and student laboratory